Desarrollo de estrategias urbanas para el mejoramiento del espacio público de la comuna 3 de la ciudad de Neiva-Huila (2021)
The city of Neiva- Huila has had a disorderly growth from the informal settlements that normally appear on the banks of the Las Ceibas and Magdalena rivers, where on many occasions they are presented by families who are uprooted from their lands in the countryside. Because of the armed conflict that plagues our country and with this the evident problems found in the Neiva community 3, on the one hand it finds the deficit and the disarticulation of public spaces and green areas and on the other hand the lack of cultural facilities and recreational in which they converge to the interaction of the different ethnic groups that inhabit Neiva. In response to these problems encountered, it proposes a planning of an urban development strategy, which contributes to the construction of society from education, culture, sports and recreation in a system of natural spaces, strengthening and empowering this sector of the city.